Analysis of entry and exit delamination during micro-drilling of green composites using response surface methodology. (10th December 2020) - Choudhury, Mridusmita Roy; Dutta, Hrishikesh; Debnath, Kishore
Micro-drilling of fibre-reinforced composites is an inevitable machining operation in the different sectors namely biomedical, aerospace, and automobile, to name a few. However, the damages induced during micro-drilling of fibre-reinforced composites due to the anisotropic and heterogeneous nature of the composite is an observable impediment. Thus, in this research endeavour, the micro-drilling behaviour of green composite composed of bamboo fibre and poly(lactic) acid (PLA) was experimentally investigated. The intrinsic effect of the process parameters namely drill diameter (300, 400, and 500 μm), feed (1, 1.5, and 2 mm/min), and tool speed (300, 400, and 500 RPM) on the induced delamination both at the entry and exit side of the hole was studied by performing response surface methodology (RSM). The drill diameter was found to be the most significant parameter affecting the induced delamination. Delamination was found to be increased with the drill diameter and decreased with the tool speed. The lower level of drill diameter (300 μm), higher level of feed (2 mm/min), and higher level of tool speed (500 RPM) was found to be the optimised parametric setting to obtain the lower value of delamination factor. The optimised delamination factors at the entry and exit sides of the hole were found to be 1.318 and 1.359.